PENGARUH DIFERENSIASI PRODUK, MEREK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK PASTA GIGI PEPSODENT DI SURABAYA - Tupen, Imelda Kewa (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Variable product differentiation, brand, price and promotion give a greatly influence on purchasing decisions of consumers. This research aims (1) To determine the effect of product differentiation on consumer purchasing decisions of pepsodent toothpaste products in Surabaya (2) To determine the effect of brand on consumer purchasing decisions of pepsodent toothpaste products in Surabaya (3) To determine the effect of price on consumer purchasing decisions of pepsodent toothpaste products in Surabaya (4) To determine the effect of promotions on consumer purchasing decisions of pepsodent toothpaste products in Surabaya. This research was conducted on people in Surabaya who become the consumer of pepsodent toothpaste products, determination of sample is 125 respondents. This research used Regresi Linier Berganda Analysis Results showed a positive effect of product differentiation on consumer purchasing decisions, brand give a positive influence to the purchasing decisions of consumers, prices have a positive effect on consumer purchasing decisions, and promotion give positive influence to the consumers' purchasing decisions. In the company, the owners of the company are expected to be able to implement product differentiation, brand, price and promotion on every product manufactured because, with so will affect consumers in making purchasing decisions and use the company's products, and can increase the profitability of the company.